Дематієві гіфоміцети як потенційні індикатори стану лісу - Мєшков Ярослав Віталійович; Фоменко, М.І. (УкрНДІЛГА, 2021)
Dematioids is a formal but common name for a polyphyletic group of fungi that previously had the status of the family Dematiaceae Fr. from the class Hyphomycetes Fr. The group includes anamorphic fungi with simple or sinnematous conidiophores and melanized sporulations. Members of this group are highly resistant to various adverse environmental factors, often live on dead wood and play a significant role in its destruction, which determines the life of forest ecosystems. They can take part either in the early stage of decomposition either in the late. The high species diversity and abundance of dematioid hyphomycetes representatives on dead fallen wood in the forest can serve as an indirect indicators of forest health. The decrease in the number and variety of dark-colored hyphomycetes on felled wood can signal a strong anthropogenic load or other extreme factors.
Mieshkov Ya.V. Fomenko M.I. Dematioid hyphomycetes as potential indicators of forest state
Keywords: гриби; індикація; ліси; Україна